High Stability Positron Beam Generation Based on Ultra-intense Laser - Lei F. (ACTA PHYSICA POLONICA A, 2020)
Relativistic positron beams were generated by laser wakefield electrons bombarding on solid target. Very stable positron beams were generated in our experiments. The total yield of positrons is about 4.4 x 10(8)/shot. The energy spectra of positrons and electrons obey quasi-Maxwell distribution. Compared with the direct method, the indirect method produces positrons (38.5 MeV) and electrons (50.5 MeV) with much higher slope temperature.